Inequalities in cardiovascular disease among elderly Indians: A gender perspective analysis using LASI wave-I (2017-18) - Bijaya K Padhi (16823745) (2024)
Background While Cardiovascular disease (CVD) affects both men and women, emerging evidence suggests notable gender differentials in disease prevalence. This study aims to explore and analyse the gender differentials in CVD disease prevalence in India. Methods The present study utilizes data from first wave of the nationally representative survey “Longitudinal Ageing Study in India” (LASI, WAVE-I, 2017-18) with the eligible sample size of 31,464 individuals aged 60 years and above. Logistic regression analysis was used to understand risk of CVD by demographic characteristics. Factors contribution to gender differences in CVD prevalence was examined using a non-linear Fairlie decomposition. Results The prevalence of CVD was lower in men (31.06%) compared to women (38.85%). Women have a 33% higher likelihood of CVD compared to men (OR: 1.33; 95% CI: 1.25-1.42). Lack of education also confers a lower risk, more pronounced in women with no schooling (OR: 0.81; 95% CI: 0.7-0.94) compared to men (OR: 0.52; 95% CI: 0.47-0.58). Morbidity influences CVD presence more among women than men, with individuals suffering from three or more diseases having markedly increased odds (Men: OR: 3.89; 95% CI: 3.54-4.3, Women: OR: 6.97; 95% CI: 6.48-10.11). Smoking accounted increase in (20.52%) the gender gap while years of schooling dramatically lessened the gender gap (-46.30%). Conclusion Result show gender differential in CVD prevalence and underlying risk factors, underscoring the need for gender-specific preventive strategies and interventions. Our findings highlight the importance of refined approach to cardiovascular health that considers the complex interplay of biological, social, and environmental determinants. Other Information Published in: Current Problems in Cardiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cpcardiol.2024.102605